PENGARUH PRAKTIKUM BERBASIS RISET TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI PERKEMBANGAN DAN PERTUMBUHAN KACANG HIJAI (Vigna radiata) PADA SISWA KELAS VIII SMP IT PLUS TAHFIDZUL QUR’AN AIKMEL - Jannatul Aeni; M Harja Efendi; Firman Ali Rahman (Jurnal Inovasi Pendidikan dan Sains, 2023)
This study aims to determine the effect of research-based practicum on students' science process skills. Quasi-experimental type with Non-Equivalent control group design. This research was conducted at SMP IT Plus Tahfidzul Qur'an Aikmel for the 2023/2024 academic year. The results of this study indicate that for the value of Sig. is 0.009 < 0.05 so that it can be seen that there are differences in learning outcomes of science process skills between research-based practicum and lecture methods. This can be observed from the very striking difference in terms of the average value obtained. In the experimental class the average posttest score of the students was 70.5. In the control class the average posttest score of the students was 56.5. There are differences in student learning outcomes in the experimental and control classes caused by internal and external factors. One of the most influential factors is the method used. The experimental class uses a research-based practicum method while the control class does not use a research-based practicum method.